Pulque, a Traditional Mexican Alcoholic Fermented Beverage: Historical, Microbiological, and Technical Aspects - Escalante, Adelfo; López Soto, David R.; Velázquez Gutiérrez, Judith E.; Giles-Gómez, Martha; Bolívar, Francisco; López-Munguía, Agustín (Frontiers in Microbiology, 2016)
Pulque is a traditional Mexican alcoholic beverage produced from the fermentation of the fresh sap known as aguamiel (mead) extracted from several species of Agave (maguey) plants that grow in the Central Mexico plateau. Currently, pulque is produced, sold and consumed in popular districts of Mexico City and rural areas. The fermented product is a milky white, viscous, and slightly acidic liquid beverage with an alcohol content between 4 - 7 °GL and history of consumption that dates back to pre-Hispanic times. In this contribution, we review the traditional pulque production process, including the microbiota involved in the biochemical changes that take place during aguamiel fermentation. We discuss the historical relevance and the benefits of pulque consumption, its chemical and nutritional properties, including the health benefits associated with diverse lactic acid bacteria with probiotic potential isolated from the beverage. Finally, we describe the actual status of pulque production as well as the social, scientific and technological challenges faced to preserve and improve the production of this ancestral beverage and Mexican cultural heritage.